Chinese modernization and the sinification of Marxism through the lens of Li Zehou's philosophy. Issue 1 (2nd January 2017) - Rosker, Jana
ABSTRACT: Li Zehou belongs to the most well-known and influential contemporary Chinese philosophers of our time. Since he is one of the exiled intellectuals, his work has also acquired a wide readership outside China. Working mostly in the fields of classical Chinese philosophy and Chinese aesthetics, he dedicated himself to the task of finding a suitable and sensible way of harmonizing past and present, tradition and modernity, China and the West. Hence, he attempted to create a synthesis between early Marxist and classical Confucian discourses. The present article offers a critical analysis of these attempts, focusing upon some significant methodological problems underlying such approaches. The author aims to explain them in the framework of the methodology of intercultural research. Because in China, the problem of connecting Confucian and Marxist thought is presently a much discussed and very topical issue, the article also represents a contribution to the clarification of this relevant question.